Tuned viscous mass damper (TVMD) coupled wall system for enhancing seismic performance of high-rise buildings. (1st August 2021) - Ji, Xiaodong; Zhang, Junshan; Ikago, Kohju; Chakraborty, Sanjukta; Kanno, Hideto
Highlights: A novel tuned viscous mass damper (TVMD) coupled wall system is proposed. Both single-mode and multi-mode tuning design methods are developed for the system. The system effectively controls drift and acceleration responses of tall buildings. Real-time hybrid simulation indicates detuning effect is slight for the system. Abstract: This paper proposes an innovative coupled wall system, named the tuned viscous mass damper (TVMD) coupled wall system, for use in high-rise buildings. This novel wall system is expected to control both the lateral inter-story drifts and the floor accelerations of high-rise buildings when subjected to strong ground motions, thus enhancing their seismic resilience. The TVMD consists of a component that provides stiffness connected in series with a ball screw device that can provide large inertial and damping forces, even when subjected to small deformations. In this system, TVMDs are arranged to connect adjacent wall piers in a zig-zag configuration. Such a strategic TVMD arrangement makes efficient use of the vertical relative displacements of the adjacent walls induced by their flexural deformation to generate the motions and forces of the TVMDs. Two methods are presented for the optimal design of this system, namely, a single-mode tuning method and a multi-mode tuning method. Dynamic response analysis is conducted on a representative 15-story TVMD coupled wall system. The results of the analysis indicate that the TVMDs designed by the single-mode tuning method not only suppress the dynamic responses of the tuning mode, but also provide additional damping for the lower-order modes of the primary structure. The multi-mode tuning method shows similar performance to the single-mode tuning method if the latter is used to tune the higher-order mode. Finally, real-time hybrid simulations were conducted to examine the seismic performance of the proposed system. The test results demonstrate the advantages of the TVMD coupled wall system and indicate that the detuning effect is slight for this system, even when subjected to strong ground motions.